Instructing cells with programmable peptide DNA hybrids - Ronit Freeman (Nature Portfolio, 2017)
The extracellular matrix can affect cell behaviour both physically and biochemically. Here, the authors developed a substrate that is based on peptides and nucleic acids hybrids that can dynamically present signals upon demand which regulate cell adhesion and migration, thereby controlling cell organisation.